A plasmonic hybrid nanostructure with controlled interaction strength - Grzelak, Justyna; Krajnik, Bartosz; Thoreson, Mark; Nyga, Piotr; Shalaev, Vladimir; Mackowski, Sebastian (Photonics Letters of Poland, 2013)
We describe a novel plasmonic hybrid nanostructure based on a silver island film covered with a dielectric silica layer. The thickness of the silica layer is varied from 0 to approximately 46 nm on a single sample, thus allowing for continuous variation of the interaction strength between plasmon excitations in the metallic film and the excited states of pigments comprising photosynthetic complexes used to probe this interaction. While the largest separation between the silver film and photosynthetic complexes provides fluorescence featuring mono-exponential decay, thinner silica spacer distances show bi-exponential decay. The intensity of the fast component, which is attributed to the emission of photosynthetic complexes coupled to plasmon excitations, strongly decreases as a function of the spacer thickness. The interaction is stronger for excitation wavelengths resonant with plasmon absorption in the metallic layer. Full Text: PDF References P. Anger, P. Bharadwaj, L. Novotny, "Enhancement and Quenching of Single-Molecule Fluorescence", Phys. Rev. Lett. 96, 113002 (2006). CrossRef M.A. Noginov, G. Zhu, M. Bahoura, C.E. Small, C. Davison, J. Adegoke, V.P. Drachev, P. Nyga, V.M. Shalaev, "Enhancement of spontaneous and stimulated emission of a rhodamine 6G dye by an Ag aggregate", Phys. Rev. B 74, 184203 (2006). CrossRef K. Ray, R. Badugu, J. R. Lakowicz, "Metal-Enhanced Fluorescence from CdTe Nanocrystals: A Single-Molecule Fluorescence Study", J. Am. Chem. Soc. 128, 8998 (2006). CrossRef W. Zhang, Y. Chen, C. Hu, Y. Zhang, X. Chen, M. Qiu Zhang, "Effective excitation and control of guided surface plasmon polaritons in a conjugated polymer–silver nanowire composite system", J. Mater. Chem. C 1, 1265 (2013). CrossRef Ł. Bujak, N. Czechowski, D. Piatkowski, R. Litvin, S. Mackowski, T.H.P. Brotosudarmo, R.J. Cogdell, S. Pichler, W. Heiss, "Fluorescence enhancement of light-harvesting complex 2 from purple bacteria coupled to spherical gold nanoparticles", Appl. Phys. Lett. 99, 173701 (2011). CrossRef J.B. Nieder, R. Bittl, M. Brecht, "Fluorescence Studies into the Effect of Plasmonic Interactions on Protein Function", Angew. Chem. Int. Ed. 49, 10217 (2010). CrossRef P. Nyga, V. P. Drachev, M.D. Thoreson, V. M. Shalaev, "Mid-IR plasmonics and photomodification with Ag films", Appl. Phys. B 93, 59 (2008). CrossRef U.K. Chettiar, P. Nyga, M.D. Thoreson, A.V. Kildishev, V.P. Drachev, V.M. Shalaev, "FDTD modeling of realistic semicontinuous metal films", Appl. Phys. B 100, 159 (2010). CrossRef V.P. Drachev, M.D. Thoreson, V. Nashine, E.N. Khaliullin, D. Ben-Amotz, V.J. Davisson, V.M. Shalaev., "Adaptive silver films for surface-enhanced Raman spectroscopy of biomolecules", J. Raman Spectroscopy 36, 648 (2005). CrossRef B. Krajnik, T. Schulte, D. Piątkowski, N. Czechowski, E. Hofmann, S. Mackowski, "SIL-based confocal fluorescence microscope for investigating individual nanostructures", Cent. Eur. J. Phys. 9, 293 (2011). CrossRef